Health and Clinical Management - From Hospital to Home Patient Care Management - Kubias, D.; Managing Editor for the IMIA Yearbook Section on Health and Clinical Management (Yearbook of Medical Informatics, 2008)
Objectives To summarize last year’s excellent research in the field of heath and clinical management.Method Synopsis of the best articles selected for the IMIA Yearbook 2008.Results The selection process for this yearbook’s section on ‘Health and Clinical Management’ results in four excellent articles representing various topics of the field. These papers cover areas from inpatient managerial decision support to remote patient monitoring at their homes.Conclusions Although these articles represent only a fraction of the worldwide work in the ‘Health and Clinical Management’ domain, they show promising strategies for contributing to improving the management of patient care.
Keywords: Medical informatics; International Medical Informatics Association; yearbook; patient care management; technology assessment